Effect of Fluid Therapy in Early Morning on the Incidence of Post-Induction Hypotension During Non-Cardiac Surgery After Noon: A Single-Center Retrospective Study - Zhang Y; Wang X; Sang X; Zhou Z; Dai G; Zhang X (Dove Medical Press, 2024)
Ying Zhang,1,* Xinxin Wang,1,* Xiaoqiao Sang,1,* Zhou Zhou,1 Guangrong Dai,1 Xiaobao Zhang1,2 1Department of Anesthesiology, The Affiliated Lianyungang Hospital of Xuzhou Medical University, Lianyungang, Jiangsu, People's Republic of China; 2The First Affiliated Hospital of Kangda College of Nanjing Medical University, Lianyungang, Jiangsu, People's Republic of China*These authors contributed equally to this workCorrespondence: Xiaobao Zhang, The Affiliated Lianyungang Hospital of Xuzhou Medical University, No. 6 Zhenhua East Road, Lianyungang, Jiangsu, People's Republic of China, Email hotdog100@163.comPurpose: Post-induction hypotension (PIH) is a common clinical phenomenon linked to increased morbidity and mortality in various non-cardiac surgeries. Patients with surgery in the afternoon may have preoperative hypovolemia caused by prolonged fasting and dehydration, which increases the risk of hypotension during the induction period. However, studies on the fluid therapy in early morning combating PIH remain inadequate. Therefore, we aimed to investigate the influence of prophylactic high-volume fluid in the early morning of the operation day on the incidence of PIH during non-cardiac surgery after noon.Patients and Methods: We reviewed the medical records of patients who underwent non-cardiac surgery after noon between October 2021 and October 2022. The patients were divided into two groups based on whether they received a substantial volume of intravenous fluid (high-volume group) or not (low-volume group) in the early morning of the surgery day. We investigated the incidence of PIH and intraoperative hypotension (IOH) as well as the accumulated duration of PIH in the first 15 minutes. In total, 550 patients were included in the analysis.Results: After propensity score matching, the incidence of PIH was 39.7% in the high-volume group and 54.1% in the low-volume group. Multivariate logistic regression analysis showed that patients in the high-volume group had lower incidence of hypotension after induction compared with the low-volume group (odds ratio, 0.55; 95% CI, 0.34- 0.89; p = 0.016). The high-volume fluid infusion in the preoperative morning was significantly correlated with the decreased duration of PIH (p = 0.013), but no statistical difference was observed for the occurrence of IOH between the two groups (p = 0.075).Conclusion: The fluid therapy of more than or equal to 1000 mL in the early morning of the surgery day was associated with a decreased incidence of PIH compared with the low-volume group in patients undergoing non-cardiac surgery after noon.Keywords: anesthesia induction, hypotension, fluid optimization, preoperative rehydration, hemodynamic instability